Answers

2015-03-24T21:27:21+05:30
We know that a^2-b^2=(a+b)(a-b)
so 87^2-13^2=(87+13)(87-13)=(100)(74)=7400
the same method is used for the other
64^2-36^2=(64+36)(64-36)=100*28=2800


1 5 1
2015-03-24T21:29:14+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
If you use the identity, then you can easily calculate it.
You are asked to find 87² - 13²
use the identity: a² - b² = (a+b)(a-b)
here a=87, b = 13

87² - 13²
= (87+13)(87-13)
= 100 × 74
= 7400

similarly to calculate 64² - 36²
a=64, b=36
64² - 36² = (64+36)(64-36) = 100 × 28 = 2800
1 5 1
bro do the 2nd one too
sorry..i didn't see that part..